Activation of alpha(2)-adrenoceptors in the lateral hypothalamus reduces pilocarpine-induced salivation in rats - Takakura, Ana C. [UNESP]; Moreira, Thiago S. [UNESP]; Colombari, Debora S. A. [UNESP]; De Luca, Laurival A. [UNESP]; Menani, José Vanderlei [UNESP] (Elsevier B.V., 2009)
Anti-hypertensive drugs that act oil central alpha(2)-adrenoceptors and imidazoline receptors usually cause dry mouth in patients. A central area important for the control of salivary secretion and also for the effects of alpha(2)-adrenoceptor activation is the lateral hypothalamus (LH). Therefore, in the present study we investigated the effects of the injections of moxonidine (ail alpha(2)-adrenoceptor and imidazoline agonist) alone or combined with RX 821002 (alpha(2)-adrenoceptor antagonist) into the LH oil the salivation induced by intraperitoneal (i.p.) pilocarpine (cholinergic muscarinic agonist). Male Holtzman rats with stainless steel cannula implanted into the LH were used. Saliva was collected using pre-weighted small cotton balls inserted into the animal's Mouth Under ketamine anesthesia. Salivation induced by i.p. pilorcarpine (4 mu mol/kg of body weight) was reduced by the injection of moxonidine (10 and 20 nmol/0.5 mu l) into the LH (222 +/- 46 and 183 +/- 19 mg/7 min, vs. vehicle: 480 +/- 30 mg/7 min). The inhibitory effect of moxonidine oil pilocarpine-induced salivation was abolished by prior injections of RX 821002 (160 and 320 nmol/0.5 mu l) into the LH (357 +/- 25 and 446 +/- 38 mg/7 min). Injections of the alpha(1)-adrenoceptor antagonist prazosin (320 nmol/0.5 mu l) into the LH did not change the effects of moxonidine. The results show that activation of alpha(2)-adrenoceptors in the LH inhibits pilocarpine-induced salivation, suggesting that LH is one of the possible central sites involved in the anti-salivatory effects produced by the treatment with alpha(2)-adrenoceptor agonists. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Pilocarpine; Salivation; alpha(2)-Adrenoceptors; Cholinergic receptors; Lateral hypothalamus